Spirituality in the Theory of Planned Behavior: Explaining Civil Servant Compliance - Arfiansyah, Moehammad Reza; Ushuluddin, Achmad (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
This study examines how spirituality influences work behavior among civil servants in the Regional Offices of Indonesia’s Ministry of Religious Affairs by applying the Theory of Planned Behavior (TPB). The study’s novel contribution lies in extending TPB by conceptualizing spirituality as a moral–evaluative belief that shapes compliance intention within a value-based bureaucratic context. Using a quantitative survey design, data were collected from civil servants across several organizational units. Work behavior is assessed through the Ministry’s Five Core Work Values: integrity, professionalism, innovation, responsibility, and exemplary conduct. The findings reveal that spirituality does not directly influence work behavior; its effect operates entirely through compliance intention as a mediating mechanism. These results demonstrate that spiritually grounded beliefs function as an antecedent of intentional compliance rather than immediate behavioral action. Strengthening employees’ spiritual meaning-making therefore becomes a strategic pathway for public institutions to reinforce ethical commitment and sustain value-consistent performance among civil servants.